Plant Adaptation to Global Climate Change - Mishra, Amit Kumar (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Plant Adaptation to Global Climate Change discusses the issues of the impact of climate change factors (abiotic and biotic) on vegetation. This book also deals with simulation modeling approaches to understanding the long-term effects of different environmental factors on vegetation. This book is a valuable resource for the environmental science research community, including those interested in assessing climate change impacts on vegetation and researchers working on simulation modeling.